Combined strategy for the dispersion/dissolution of single walled carbon nanotubes and cellulose in water - Adsul, Mukund G.; Rey, Diego A.; Gokhale, Digambar V. (Journal of Materials Chemistry, 2011)
Co-dispersion of native cellulose and single walled carbon nanotubes in water is demonstrated. The pH of the water should be between 6 and 10 for better dispersion. Raman spectra confirm debundling of nanotubes in water and FTIR spectra reveal that the co-solubility is likely caused through disruption of intramolecular hydrogen bonds in the cellulose by hydroxyl groups present on nanotubes surface and the creation of intermolecular hydrogen bonds between cellulose and carbon nanotubes. This is a very simple method for co-dispersion/dissolution of nanotubes and cellulose in water without covalent modifications and expands the repertoire of nanotube modification strategies that are amenable to biological applications.